2019
DOI: 10.1007/s10865-019-00061-0
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept trial for a new theory-based intervention to promote child and adult behavior change

Abstract: Interventions to change children's behavior typically target adults or children, but rarely both. The aims were to: (a) evaluate acceptability and feasibility of an innovative theory-based intervention designed to change both child and adult behavior, and (b) generate effect sizes for a definitive randomized controlled trial. The oral health of sixty children aged 5-9 years with a repaired cleft lip and/or palate was assessed before randomization to one of three conditions: (a) control group, (b) intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Plaque scores in the 0–2-year olds varied substantially and were more difficult to undertake, which is unsurprising given the behavioural management challenges in this younger age group. This is consistent with other interventional studies that have found a bigger improvement in plaque scores in older children [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Plaque scores in the 0–2-year olds varied substantially and were more difficult to undertake, which is unsurprising given the behavioural management challenges in this younger age group. This is consistent with other interventional studies that have found a bigger improvement in plaque scores in older children [ 45 ].…”
Section: Discussionsupporting
confidence: 93%
“…Plaque scores in the 0-2-year olds varied substantially and were more di cult to undertake, which is unsurprising given the behavioural management challenges in this younger age group. This is consistent with other interventional studies that have found a bigger improvement in plaque scores in older children 45 .…”
Section: Plaque Scoressupporting
confidence: 93%
“…While intuitive, this observation has methodological implications for studies employing single session experimental designs. Single session proof-of-concept studies are often used when exploring the merit of new intervention approaches or testing the implications of parameter modifications ( Armitage et al, 2020 ; Radley-Crabb et al, 2012 ; Turton et al, 2018 ). That the current meta-analysis found no evidence of effects on inhibitory control following a single session of combined physical and cognitive training indicates that either more sessions are needed for modulation to occur, or far more sensitive outcome measures are required to detect subtle effects.…”
Section: Discussionmentioning
confidence: 99%